PENGEMBANGAN MEDIA SCRAMBLE BERBANTUAN WORDWALL UNTUK MATERI KALMAT SPO KELAS II SD - Apriani, Ni Luh; Ariasa Giri , I Made; Jaya Suryawan , IG Agung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low understanding of SPO sentence structure of second-grade students at SDN 1 Astina and the limited technology-based learning media used in Indonesian language learning. This research aims to describe the design, validity, and practicality of interactive digital media Scramble assisted by Wordwall on SPO sentence material. The type of research used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Research data were collected through observation, interviews, questionnaires, and documentation. Validation was carried out by six expert lecturers and one teacher. The practicality test involved two teachers, one principal, and 14 second-grade students at SDN 1 Astina. The results of the study show that: (1) the media was developed through ADDIE stages to produce an interactive flipbook containing Scramble material, exercises, videos, and quizzes; (2) the validity results obtained a score of 0.92 from media experts, 0.92 from material experts, and 0.94 from language experts, all of which are categorized as very valid; and (3) the results of practicality obtained a percentage of 89% from teachers and 96% from students, both of which were categorized as very practical. Thus, the interactive digital media Scramble assisted by Wordwall was declared valid and very practical to use in learning Indonesian language material SPO sentences in grade II of elementary school. The implications of this study indicate that the use of interactive digital media Scramble assisted by Wordwall can be an innovative alternative for teachers in creating more interesting, interactive, and student-centered learning, thus potentially increasing students' understanding of SPO sentence structures and supporting the use of technology in learning in elementary schools.